PENERAPAN STRATEGI MNEMONIK KEYWORD DALAM MENINGKATKAN PEMAHAMAN KOSA KATA SISWA TUNARUNGU DI SLB X LEMBANG - Nofita, Deni (2014)
The aim of this research is to find the application of keyword mnemonic strategy in improving hearing-impaired students' vocabulary comprehension. One of the advantages of mnemonic strategies is to facilitate memorization. Keyword method is one of mnemonic strategies classified as linguistic mnemonic, which is aimed to facilitate memorization, especially new or foreign vocabulary, by means of connecting pictures to words whose pronunciations are similar to the words or concepts that should be memorized. The research employed experimental method using Single Subject Research (SSR) with A-B-A design. The subjects were hearing-impaired students aged fifteen years old, namely A and DL, who were in the fifth and sixth grade of Special Needs School X Lembang, respectively. The results of the research showed that there was improvement in terms of vocabulary comprehension using keyword mnemonic strategy as measured by verbal/gesture test. The ability of subject A in re-expressing words' definitions through verbal/gesture test during the phase of baseline 1 gained a mean level of 65%, during intervention phase 91.85%, and during baseline 2 phase 92.33%, respectively, which showed improvement. Meanwhile, the ability of subject DL as measured by verbal/gesture test was as follows: during the phase of baseline 1, the mean level was 36.42%, intervention phase 76.28%, and baseline 2 as much as 92.33%. This means that DL's ability as measured by verbal/gesture test improved. The outcomes of the research demonstrate that keyword mnemonic strategy can be applied to hearing-impaired students to improve vocabulary comprehension. Therefore, it is suggested that teachers apply keyword mnemonic strategy in the classroom instruction and that future researchers can refine the shortcomings of this research, such as by measuring the ability of hearing-impaired students in re-expressing words' definitions through writing. In addition, a test is needed with considerations of subjects' conditions, age, and ability differences, and an involvement of a larger population.